Penguatan Kesadaran Warga Negara Tentang Pentingnya Menjaga Kebersihan Lingkungan di Desa Kuma Kecamatan Tabukan-Tengah - Susi Julianti Kundimang; Apeles Lexi Lonto; Julien Biringan (Tumoutou Social Science Journal, 2026)
This study aims to find out why students at SMK Negeri 1 East Siau are still found to have less disciplined behavior and to find out teachers' efforts to improve the disciplinary character of SMK Negeri 1 Siau Timur students. The method used in this study is qualitative. The qualitative method is a naturalistic research method because the research is carried out under natural conditions. Where the researcher is the key instrument, the data collection technique is carried out in a triangulation (combined) manner, the data analysis is also inductive/qualitative, and the results of the research emphasize more on meaning and generalization. The results of the study show that the level of awareness of the people of Kuma Village regarding environmental cleanliness in general can be categorized quite well, although this has not been achieved evenly among the entire community. This is reflected in the participation of some people in efforts to maintain cleanliness, such as throwing garbage in the places that have been provided, cleaning the area around their homes, and participating in social service activities that are held regularly. However, there are still some people who do not care, as can be seen from the garbage that is thrown carelessly in various locations, including beaches, irrigation canals, yards, and mangrove areas. This condition shows the need to increase mutual understanding and awareness of the urgency of maintaining environmental cleanliness through education, socialization, and sustainable capacity building programs. In addition, closer cooperation is needed between the village government and the community to foster a sense of shared responsibility, so that a clean, healthy, and beautiful village environment is realized.